Comprehensive Physiology 2014
DOI: 10.1002/cphy.c140037
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Conditioning of the Vasculature

Abstract: There is increasing evidence from epidemiological and experimental animal studies that the early life environment, of which nutrition is a key component, acts through developmental adaptive responses to set the capacity of cardiovascular and metabolic pathways to respond to physiological and pathophysiological challenges in later life. One finding that is consistent to both population studies and animal models is the propensity for such effects to induce endothelial dysfunction throughout the vascular tree, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 472 publications
1
7
0
Order By: Relevance
“…For example, NO mediates vascular relaxation of 327 relatively large, conduit arteries, whereas endothelium-derived 328 hyperpolarization factors (EDHF) play a crucial role in the 329 relaxation of small (resistant) arteries [69]. 330 One of the major stimuli linked to exercise-induced vasodila-331 tion is shear stress, a frictional force along endothelial cell 332 membranes exerted by blood flow [70].…”
mentioning
confidence: 99%
“…For example, NO mediates vascular relaxation of 327 relatively large, conduit arteries, whereas endothelium-derived 328 hyperpolarization factors (EDHF) play a crucial role in the 329 relaxation of small (resistant) arteries [69]. 330 One of the major stimuli linked to exercise-induced vasodila-331 tion is shear stress, a frictional force along endothelial cell 332 membranes exerted by blood flow [70].…”
mentioning
confidence: 99%
“…The vasculature is sensitive to perturbations in the early‐life environment and adaptations made in this system can predispose to later cardiovascular disease (Clough, ). In the present study, passive stiffness of mesenteric and renal arteries was not different between Control and Restricted male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…, ; White et al . ; Clough, ). Uteroplacental insufficiency is the most common cause of fetal growth restriction in Western nations and affects around one in ten pregnancies (Henriksen & Clausen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, it was recently suggested that the pro‐inflammatory and pro‐oxidant conditions observed in post‐capillary venules may be the initiating site for microvascular rarefaction that is commonly associated with chronic metabolic disease (Gilbert, ; Frisbee et al . ; Clough, ) and that fluid handling across the microcirculation may be altered by chronic impairments to glycaemic control (Huxley & Scallan, ; Scallan et al . ).…”
Section: Discussionmentioning
confidence: 99%